2013
DOI: 10.1021/ac402078p
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acidomics: Global Analysis of Lipid Species Containing a Carboxyl Group with a Charge-Remote Fragmentation-Assisted Approach

Abstract: Charge-remote fragmentation has been well recognized as an effective approach for dissociation of long aliphatic chains. Herein, we exploited this approach for structural identification of all fatty acids including saturated, unsaturated, and modified ones by using electrospray ionization tandem mass spectrometry (ESI-MS/MS) after one-step derivatization of a charge-carried reagent through an amidation reaction. We tested the approach with different charge-carried reagents with respective to the hydrophobicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 34 publications
7
165
0
Order By: Relevance
“…In this study, we identified and characterized two novel ϖ-hydroxy docosahexaenoids, 14 S ,22-diHDHA and 14 R ,22-diHDHA, which are generated from DHA by leukocytes and/or PLT. We performed structural elucidation by aR chiral LC-UV-MS/MS spectroscopy and chromatography including use of deuterium-labeled isotopomers (Wang et al, 2013). The chiralities of the two 14,22-diHDHA stereoisomers were identified.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified and characterized two novel ϖ-hydroxy docosahexaenoids, 14 S ,22-diHDHA and 14 R ,22-diHDHA, which are generated from DHA by leukocytes and/or PLT. We performed structural elucidation by aR chiral LC-UV-MS/MS spectroscopy and chromatography including use of deuterium-labeled isotopomers (Wang et al, 2013). The chiralities of the two 14,22-diHDHA stereoisomers were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Lipidomics were performed as reported previously (4,47,75). Briefly, wounded skin was extracted three times with cold methanol:butylated hydroxytoluene (1:0.005%).…”
Section: Methodsmentioning
confidence: 99%
“…6 ) ( 34, 40-43 ), and ions from charge-remote fragmentations can locate the methyl side chains ( 34,43 ) and the functional groups unambiguously ( Fig. 6 , inset).…”
Section: Characterization Of Multiple-methyl-branched Long-chain Mycomentioning
confidence: 96%
“…By contrast, the traditional GC/MS method for identifi cation of mycocerosic acids is laborious, requiring acid methanolysis to form the methyl ester, separated by TLC, followed by reductive degradation to mycocerosic alcohol and another two-dimensional TLC purifi cation, before formation of the fi nal t-butyldimethylsilyl ether derivatives (23)(24)(25). The superb sensitivity gained for the acid detected as the AMPP derivative (as compared with its underivatized form) also facilitates structural identifi cation and quantitation ( 34,(40)(41)(42)(43). This aspect may deserve further investigation.…”
Section: Characterization Of Multiple-methyl-branched Long-chain Mycomentioning
confidence: 99%